2019
DOI: 10.1186/s13104-019-4155-x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and adverse perinatal outcomes of low birth weight newborns delivered in Hawassa University Comprehensive Specialized Hospital, Ethiopia: a cohort study

Abstract: Objective: Globally an estimated 15% to 20% of all births are low birth weight, representing more than 20 million births a year. Low birth weights are at a greater risk of both short and long-term sequels. Therefore, this study was conducted to assess determinants and perinatal outcomes of low birth weight newborns delivered in Hawassa University Comprehensive Specialized Hospital, Southern Ethiopia. Results: A total of 420 mothers were included in the study with a response rate of 97%. The mean birth weights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
(47 reference statements)
2
21
0
Order By: Relevance
“…This can be due the reason that hypertension results in uteroplacental insufficiency. Similarly, the studies also reported that mothers who had fewer ANV visit than the WHO recommendations (<4 ANC visit) were more likely to give a low-weight newborn than those who adhered to the recommended ANC visits, who have more than four times [28]. This is also supported by other evidences [36,40,47].…”
Section: Obstetrical Factorssupporting
confidence: 68%
See 4 more Smart Citations
“…This can be due the reason that hypertension results in uteroplacental insufficiency. Similarly, the studies also reported that mothers who had fewer ANV visit than the WHO recommendations (<4 ANC visit) were more likely to give a low-weight newborn than those who adhered to the recommended ANC visits, who have more than four times [28]. This is also supported by other evidences [36,40,47].…”
Section: Obstetrical Factorssupporting
confidence: 68%
“…In addition, findings also showed that those women who have at least one previous abortion were at greatest risk of giving LBW neonates as evidenced by a study done in Ethiopia [28], Denmark, and the USA [49,50] and a meta-analysis in Canada [17]. The report also in-line with the study by Bossley [51] showed that women who had an abortion in the first or second trimester had a 35% increased risk of a LBW baby and a 36% raised risk of a preterm baby in later pregnancies and Ethiopia [52] found that previous adverse pregnancy outcomes were associated with recent outcome.…”
Section: Obstetrical Factorsmentioning
confidence: 80%
See 3 more Smart Citations